2016
DOI: 10.5530/jppcm.2016.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rational Drug Use at Teaching Hospitals in Punjab, Pakistan

Abstract: Introduction: Rational drug use is a function of prescription practices having medical, social, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
14
1
1
Order By: Relevance
“…In absolute terms the level of adequately labelled medicines was better than reported in studies conducted in Egypt, Northern Nigeria, Pakistan and Ethiopia [58], however labelling of medicines remains sub-optimal (<50%).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In absolute terms the level of adequately labelled medicines was better than reported in studies conducted in Egypt, Northern Nigeria, Pakistan and Ethiopia [58], however labelling of medicines remains sub-optimal (<50%).…”
Section: Discussionmentioning
confidence: 59%
“…Studies conducted in Egypt, Northern Nigeria, Pakistan and Ethiopia have reported between 0 and 13.7% of dispensed medicines with adequate labels [58]. Yet in these same studies 55 to 94% of patients were reported to have adequate knowledge of the correct dose of the medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, patient's knowledge of the correct dosage of drugs was low (54.98%) compared with the desirable value of 100%. [10] According to a journal average Percentage of generic drug prescribed was 29.7% that is not according to the WHO standard values which was 100% it shows the greater interest of doctors to brand name prescribing. The average percentage of antibiotics prescribed was 64% while WHO international networking for rational use of drugs (INRUD) devised limit up to 30% that showed all health facilities contributing to bacterial resistance to antibiotics.…”
Section: Clarity In Instructions 82mentioning
confidence: 97%
“…Higher percentages were found in studies conducted in Brazil which was 86.1% 11 , in rural area of India which was 89.88% 18 , in Warangal -India which was 97.7% 21 , in South Ethiopia which were 98.7% 10 and 95.8% 16 , and in Saudi Arabia which was 100% 15 . On the other hand, lower percentages are found in studies conducted in in Goa -India which was 0.05% 12 , in Southern India which was 2.5% 20 , in Pakistan which was 39.5% 17 , in South India which was 42.9% 14 , in Western China which was 64.12% 9 , and in West Ethiopia which was 79.2% 13 .…”
Section: Percentage Of Drugs Prescribed By Generic Namementioning
confidence: 82%
“…Prescribing indicators have been applied in several studies at different level of health facilities of primary healthcare and referral healthcare in different regions of the world. Some of the studies included the studies conducted at village health clinics in Western China 9 , at teaching hospital in South Ethiopia 10 , at different level of health care in Brazil 11 , at teaching hospital in Goa -India 12 , at four hospitals in West Ethiopia 13 , at secondary care referral hospital in South India 14 , at four government hospitals in Saudi Arabia 15 , at other four hospitals in South Ethiopia 16 , at four teaching hospitals in Pakistan 17 , at teaching hospital in rual area of India 18 , at general hospitals in East Ethiopia 19 , at community pharmacies in Southern India 20 , and at private hospital in Warangal -India 3.45 21 .…”
Section: Introductionmentioning
confidence: 99%